-Mineralogy, rare earth elements geochemistry and genesis of the Keban-West Euphrates (Cu-Mo)-Pb-Zn skarn deposit (Eastern Taurus metallogenic belt, E Turkey) - Yildirim, Esra; Yildirim, Nail; Donmez, Cahit; Koh, Sang-Mo; Gunay, Kurtulus (Elsevier, 2019)
The Keban-West Euphrates (Cu-Mo)-Pb-Zn skarn deposit occurs mainly around the contact zone of the PermoTriassic/Permo-Carboniferous metamorphic rocks and Late Cretaceous plutonic rocks in the Eastern Taurus orogenic belt. The skarn formation, in this orogenic belt formed by the Hercynian and Alpine progenies, is associated with Late Cretaceous alkali syenite intrusion of calcareous rocks. The syenite intrusion is characterised by temporal and spatial zonation, producing several stages of skarnisation. The initial contact metamorphism formed broad halos of hornfels and marble. Subsequent metasomatism by high temperature and hypersaline fluids formed anhydrous talc-silicate assemblages (garnet, pyroxene and wollastonite), partially overprinted by lower temperature and saline fluid hydrous assemblages (epidote, chlorite and calcite) and sulphide minerals (mainly pyrite) as the concentration of sulphur increased. The ore skarn assemblage like pyrite, chalcopyrite, molybdenite, sphalerite, galena, fluorite, magnetite, pyrrhotite, fahlore and native gold occurs as ore minerals, whereas garnet, pyroxene, calcite, epidote, chlorite and quartz constitute the main gangue minerals. The Keban plutonic rocks are syenitic in composition with high contents of Al2O3, Na2O + K2O, Zr, Nb, Ta, Th, Rb and rare earth elements (REEs). The major and trace elements composition of the Keban pluton is consistent with those of Zn-Cu-Mo-W skarn plutons. The skarn litho-units show higher concentrations of light REEs compared with heavy REEs. The skarn zone samples display the most prominent REE-enriched pattern, and the depletion pattern in the ore zone is only subordinate to that of the host rock (limestone). The La/Y ratios of the West Euphrates skarns vary from 0.9 to 26.4 with the highest ratios in the ore zone (average = 13.35). The ratios of the plutonic rocks and skarn zones reflect near-neutral to alkali conditions, whereas the ore zone and host rock ratios are characteristic of alkali conditions. The garnet-dominated endoskarn shows high contents of REE (Sigma REE) compared with the metaluminous syenite porphyry-hosted exhibiting Eu and Ce enrichment, indicating derivation of the magmatic fluids for skarnisation from the alkali syenitic magma. Conversely, the limestones show lower REE concentrations relative to the metaluminous syenite porphyry-hosted rocks. The calcic exoskarn (garnet and cllnopyroxene) and ore zone containing high EREE, significant positive Eu and Ce anomalies and high P-r/Yb-(n) ratios are dominantly of magmatic origin.
Keywords: (Cu-Mo)-Pb-Zn skarn deposits; Rare earth elements; Syenitoid; Keban; Turkey